2023
DOI: 10.1212/wnl.0000000000207088
|View full text |Cite|
|
Sign up to set email alerts
|

Baseline Clinical and Blood Biomarkers in Patients With Preataxic and Early-Stage Disease Spinocerebellar Ataxia 1 and 3

Abstract: Background and Objective:In spinocerebellar ataxia, ataxia onset can be preceded by mild clinical manifestation, cerebellar and/or brainstem alterations or biomarkers modifications. READISCA is a prospective, longitudinal observational study of patients with spinocerebellar ataxias type 1 and 3 to provide essential markers for therapeutic interventions. We looked for clinical, imaging or biological markers that are present at an early-stage of the disease.Methods:We enrolled carriers of a pathologicalATXN1orAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Despite that, supporting evidence comes from a recent study from the READISCA consortium, which reported sensory deficits to be conspicuous and precocious in both ataxic and preataxic SCA1 and SCA3 cohorts. 18 Moreover, results from electrophysiological studies-particularly evoked potentialsare also supportive of our hypothesis. Indeed, patients with SCA1 typically present motor-evoked potentials with prolonged central conduction times, and patients with SCA1, SCA2 and SCA3 all present abnormal somatosensory-evoked potentials.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Despite that, supporting evidence comes from a recent study from the READISCA consortium, which reported sensory deficits to be conspicuous and precocious in both ataxic and preataxic SCA1 and SCA3 cohorts. 18 Moreover, results from electrophysiological studies-particularly evoked potentialsare also supportive of our hypothesis. Indeed, patients with SCA1 typically present motor-evoked potentials with prolonged central conduction times, and patients with SCA1, SCA2 and SCA3 all present abnormal somatosensory-evoked potentials.…”
Section: Discussionsupporting
confidence: 82%
“… 4 Indeed, Tezenas du Montcel and colleagues showed that pyramidal signs and posterior column signs precede ataxia in SCA1 and SCA3, suggesting that spinal cord is damaged early in these disorders. 18 Spinal MRI research undertaken in SCAs to-date has been restricted to a small number of studies that have relied on modest sample sizes, limiting the sensitivity, reliability and generalisability of available evidence. 11–13 15 17 19 Furthermore, magnitude of spinal cord damage in each SCA and how it progresses along the disease course, including in preataxic disease stages, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated NfL levels were observed in various clinical phenotypes, including isolated sensory neuropathy, which is more common in early disease stages. NfL levels demonstrated excellent discriminatory power, supporting its potential as a reliable biomarker in various neurodegenerative ataxias, 12,13,17‐19 as well as in hereditary neuropathies 8,10 …”
Section: Discussionmentioning
confidence: 85%
“…An explanation of this phenomenon is that NfL may increase rapidly in the initial stages of the disease and then reach a plateau above a certain degree of severity, as observed in other genetic ataxias. 12 , 13 , 18 Other possible explanations entail the difficulty in accurately defining the onset of the disease, because neuropathy symptoms may remain unnoticed for a long time, or the chronologically variable involvement of the cerebellum in early or late disease stages relative to onset, due to factors yet to be explored, including the repeat size and additional genetic modifiers. Also, no significant difference in serum NfL levels was found based on vestibular involvement.…”
Section: Discussionmentioning
confidence: 99%